Human tooth pulp anatomy visualization by 3D magnetic resonance microscopy - Šušterčič, Dušan (Radiology and oncology (Ljubljana), 2012)
Background. Precise assessment of dental pulp anatomy is of an extreme importance for a successful endodontic treatment. As standard radiographs of teeth provide very limited information on dental pulp anatomy, more capable methods are highly appreciated. One of these is 3D magnetic resonance (MR) microscopy of which diagnostic capabilities in terms of a better dental pulp anatomy assessment were evaluated in the study. Materials and methods. Twenty extracted human teeth were scanned on a 2.35 T MRI system for MR microscopy using the 3D spin-echo method that enabled image acquisition with isotropic resolution of 100 m. The 3D images were then post processed by ImageJ program(NIH) to obtain advanced volume rendered views of dental pulps. Results. MR microscopy at 2.35 T provided accurate data on dental pulp anatomyin vitro. The data were presented as a sequence of thin 2D slices through the pulp in various orientations or as volume rendered 3D images reconstructed form arbitrary view-points. Sequential 2D images enabled only anapproximate assessment of the pulp, while volume rendered 3D images were more precise in visualization of pulp anatomy and clearly showed pulp diverticles, number of pulp canals and root canal anastomosis. Conclusions. This in vitro study demonstrated that MR microscopy could provide very accurate 3D visualization of dental pulp anatomy. A possible future application of the method in vivo may be of a great importance for the endodontic treatment.